Sex-specific differences in echocardiographic parameters of risk stratification in pulmonary arterial hypertension - Benjamin, Nicola; Schiffer, Veronika; Resag, Carolin; Xanthouli, Panagiota; Braun, Moritz; Harutyunova, Satenik; Eichstaedt, Christina; Egenlauf, Benjamin; Marra, Alberto M.; Bossone, Eduardo; Cittadini, Antonio; Kiely, David G.; et al. (Journal of the American Society of Echocardiography, 2025)
Background - In healthy subjects, sex differences in right heart function have been detected for various echocardiographic parameters. The objective of this study was to investigate sex differences in echocardiographic European Society of Cardiology (ESC)/European Respiratory Society (ERS) risk stratification parameters and their impact on survival estimation in patients with pulmonary arterial hypertension (PAH). - Methods - In this retrospective, cross-sectional study with a mean follow-up time of 3.2 ± 2.65 years (median, 2.78 years), clinical parameters including right atrial (RA) area, right ventricular area, and tricuspid annular plane systolic excursion (TAPSE) divided by systolic pulmonary artery pressure (sPAP) were assessed. Thresholds of ESC/ERS risk stratification were compared using multivariable Cox regression analysis. - Results - Of 748 patients with PAH (mean age, 65 ± 15 years; 63% women), men had significantly larger right heart size than women (RA area 21.76 ± 7.64 vs 17.65 ± 6.82 cm2, P < .001; right ventricular area 24.02 ± 7.15 cm2 vs 18.41 ± 5.75 cm2, P < .001). This difference was consistent throughout all World Health Organization functional classes and cardiac index risk groups, except for the RA area in the cardiac index high-risk group and World Health Organization functional class IV. On multivariable analysis, indexed values showed more pronounced differences for age-adjusted survival analysis compared with ESC/ERS risk stratification thresholds. TAPSE/sPAP showed no significant sex differences, which makes this parameter a robust prognostic predictor. - Conclusions - This is the first study focusing on sex differences in right heart size obtained by echocardiography in patients with PAH. For risk stratification indexing RA area to body surface area could be more reflective of body composition. In contrast, TAPSE/sPAP values were not sex dependent and were a robust prognostic factor in patients with PAH.
Online verfügbar: 18. Dezember 2024, Artikelversion: 03. März 2025
Gesehen am 26.08.2025